Effects of Green Tea and Curcumin on Non-Enzymatic Antioxidants in Normal Mice - Elsayed, Ata Sedik Ibrahim (Pakistan Journal of Nutrition, 2015)
Flavonoids have been found to play important roles in the non-enzymatic protection against oxidative stress, especially in case of cancer. Flavonoids are group of polyphenolic compounds that occur widely in fruit, vegetables, tea, cocoas and red wine. Flavonoids, including flavones, flavanone, flavonols, flavanols and isoflavones, are polyphenolic compounds which are widespread in foods and beverages and possess a wide range of biological activities, of which antioxidation has been extensively explored. This study aimed to investigate the protective and the ameliorative role of some natural products on non-enzymatic antioxidants. Green tea extract and powdered curcumin were chosen as antioxidant natural products. CD1 mice were taken as experimental model. Green tea extract was provided to mice as their sole source of drinking water and powdered curcumin was added to the diet, these were taken for four weeks. Total thiol, protein-bound thiol and nonprotein-bound thiol, were measured in brain tissue homogenate as non-enzymatic antioxidant. The results of the study concluded that, green tea extract and curcumin addition to diet ameliorate and increase the concentration of non-enzymatic antioxidants, specially protein-bound thiol.